Are Corporate Tax Reductions Real Benefits under Imputation Systems?. Issue 2 (3rd April 2017) - Chang, Chia-Wen; Chen, Ming-Chin; Chen, Vincent Y.S.
Abstract: Imputation systems integrate corporate and shareholder personal income taxes to alleviate double taxation of dividend income. In this study, we empirically examine whether a corporate tax rate reduction under an imputation tax system benefits shareholders. Using Taiwan as a setting, our analyses indicate that decreasing the corporate tax rate is associated with an increase in dividend payout ratio and foreign investment. Moreover, the increase in dividend payout ratio is even greater for firms that have a higher increase in foreign ownership. Additionally, the market reacts positively to an announcement of a tax rate reduction; specifically, positive stock price reactions are stronger for firms that experienced a greater increase in foreign ownership in response to the tax rate reduction, for firms with greater liquidity constraints and more growth opportunities before the tax rate reduction, and for firms with a bigger decrease in effective tax rates after the tax rate reduction. Overall, we provide evidence that a tax rate reduction is associated with economic impacts and that foreign shareholders appear to be the main beneficiaries of a tax rate reduction under an imputation tax system.